PENGARUH TINGKAT PENDIDIKAN ORANG TUA TERHADAP MOTIVASI BELAJAR SISWA DI SD NEGERI 11 TANAH ABANG - Yuni Marlina; Taqwatul Uliyah; Riskun Iqbal (UNISAN JURNAL, 2024)
Research with the title "The Influence of Parental Education Level on Student Learning Motivation at SD Negeri 11 Tanah Abang. Problem Identification is 1) Students' learning motivation is low. 2.) Parents pay less attention to their children's learning. 3. ) Parents are busy with work. 4.) The education level of parents tends to be low. To collect data relevant to this research, the Questionnaire method, Documentation Method, Observation Method, Interview Method is used. The next step is to process or analyze the data to prove or test the hypothesis that has been formulated. The analysis method used is in this research is the Percentage, Chi Square analysis method of education on student learning motivation at SD Negeri 11 Tanah Abang, the author draws the following conclusions: That the learning motivation of students at SD Negeri 11 Tanah Abang shows that as many as 54 students have high learning motivation and as many as 61 students have low learning motivation. motivation to learn. . Based on the author's analysis, it can be seen that there is an influence between the level of parental education on the learning motivation of Muhammadiyah 1 Kalianda Middle School students because the interpretation value is very strong, namely 25.968.